Analysis Of The External Cause Code Accuracy Case Of Injury In General Hospital PKU Muhammadiyah Bantul - kori puspita ningsih (Jurnal Rekam Medis dan Informasi Kesehatan, 2023)
The assignment of diagnosis codes and procedures must be done correctly to ensure the quality of medical records is met. What is often forgotten when giving a diagnosis code is the secondary code or external cause. This research aims to determine the recording, implementation and level of accuracy of external cause codes. Descriptive research method with a cross sectional design. The research sample was 48 injury medical record files. The research results showed that external cause information was documented on triage forms, emergency department assessments, initial adult inpatient nursing assessments, integrated patient progress notes, and discharge summaries. External cause coding is carried out by a coder with a medical record background in accordance with the SOP for coding implementation using electronic ICD-10 contained in SIMRS. The level of accuracy of the external cause code up to the 5th character (Category A) is 0%, the 4th character (Category B) is 38%, the 3rd character (Category C) is 27%, and the 1st character (chapter) (Category D) of 35%. The reason for the inaccuracy is because SIMRS does not accommodate coding up to the fifth character and the SPO does not yet indicate the officer's activity steps to determine up to the 5th character sub-category. It can be concluded that the accuracy of external cause coding at RSU PKU Muhammadiyah Bantul falls into the Fair criteria with an accuracy range of 20-40%.